Peningkatan Tata Kelola TI di BPS Manado: Kajian Implementasi Framework COBIT 2019 - Tangka, George Morris William; Lompoliu, Erienika (TeIKa, 2024)
Information Technology (IT) governance is a framework used by organizations to effectively manage and control their information technology resources, aiming to maximize business value. The Central Statistics Agency (BPS), in its responsibility to provide critical data, faces challenges in optimizing their IT management. This research aims to apply the COBIT 2019 framework as a structure to improve Information Technology (IT) governance at BPS, facilitating efficient and smooth management of critical data services. The findings of this research reveal that BPS has not carried out a comprehensive assessment of Information Technology (IT) governance. Apart from that, there are challenges in managing order data and stock information. In addition, BPS requires a more structured information technology governance process to ensure targeted and effective use of technology, so that companies can achieve their goals more efficiently. The literature review process helps in identifying gaps in current research, paving the way for more comprehensive and insightful research. After conducting calculations for the analysis of objectives APO13 and DSS04, different results were obtained. In APO13, the questions asked only reached level 3, which means it stopped below 85%, specifically at 66%. Meanwhile, in DSS04 the questions asked continued up to the last level with a consistently high percentage, above 85%. By integrating these findings into the research, this study becomes enriched with a strong theoretical foundation, ensuring an in-depth and rigorous analysis of this issue.